MANAJEMEN OLAHRAGA PENCAK SILAT DI KABUPATEN PURBALINGGA TAHUN 2022 - Rafie Dimas Prabowo; Soedjatmiko Soedjatmiko (Unnes Journal of Sport Sciences, 2023)
Pencak silat in Purbalingga has a decline in performance and results that are not good enough in the 2014 and 2018 provincial events seen from the data on medal achievements. From these problems, the author conducted research on the management function of pencak silat sports in Purbalingga Regency. This research was used a qualitative descriptive method. Data collection in this research was used interviews method, questionnaires and documentation. Data analysis was carried out by reducing data, presenting data and drawing conclusions The research results of pencak silat sports management in Purbalingga on 2022 are: 1) Pencak silat sports planning is in good category, 2) Organizing pencak silat sports is in good category, 3) The implementation of pencak silat sports is in sufficient category, 4) Controlling of pencak silat sports is in sufficient category. The suggestion of this research is to suggest the management of IPSI Purbalingga in the management of pencak silat sports in order to remedy the quality and continue to strive to maintain the quality of organization that already good by applying the aspects of management knowledge so that it can reach IPSI Purbalingga's mission, that is creating pencak silat as a superior sport in Purbalingga.